Pengujian Aplikasi Sistem Informasi Laboratorium Kesehatan Daerah DKI Jakarta Secara Black Box - Erwin Agustian; Aditya Wirawan Pamungkas; Eky Rachman; Sri Mulyati; Yulianti Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
The use of information technology in supporting work has increased, but it is not uncommon for employees to find problems in their daily work. Problems faced include loss of documents, reporting of results that are not well documented, reporting that is still not up-to-date. The use of software in the Regional Health Laboratory of DKI Jakarta Province also has the possibility of errors. To provide a guarantee that the software used is free from errors, it is necessary to do testing. With testing, it is hoped that the software used will not cause problems and can provide convenience in daily work, can provide speed and stability in completing work, can provide good documentation results and provide the latest data and complete customer data. The test results show that the software used is error-free because the errors found have been corrected.